3PL Implementing Corporate Social Responsibility in A Closed-loop Supply Chain : A Conceptual Approach - Jonas C.P. Yu (International Journal of Supply Chain Management, 2016)
The responsibility of todays's reputable company are not only financial, but also corporate social responsibility(CSR). With regards to the environmental aspect, the public expects green logistics solutions. This paper focuses on how a third party logistics provider(3PL) might provide green logisticsservices through actions that foster sustainability. The methodology used is an in-depth interviewing approach, which described green logistics through the key drivers using depth interviews. An existing conceptual model is used to support our concepts and ideas. Finally, we discuss out the key factors from respondent regarding how to maintain sustainability through action, from 3PL's perspective. We also discuss the benefits and challenges to green logistics in future.